Observation of sub-mesoscale eddies over baltic sea using Terrasar-X and oceanographic data - Tavri, Aikaterini; Singha, Suman; Lehner, Susanne; Topouzelis, Konstantinos (European Space Agency (Special Publication) ESA SP, 2016)
Sub-mesoscale eddies are spiral like manifestations, detected on sea surface with apparent scales ranging from 1 to 10 km. These formations seem to be highly connected to the local circulation and transport processes and present size variations. The origination and the formation mechanism of these phenomena varies due to different climate conditions and until today is not completely understood. Using satellite images the detection and study of these formations is possible due to the unique abilities of different sensors and data availability. The main objective of the present study is to provide an extensive analysis on the occurrence and statistics of small-mesoscale oceanic eddies over the Baltic Sea region, using a combination of synthetic aperture radar (SAR), Sea Surface Temperature (SST), chlorophyll-A (MODIS), wind and current model data (BSH). The study area is characterized by special conditions due to strong stratification and brackish waters, which led to interesting results about the nature and the generation mechanisms of the spirals. For the present study, 1329 Terra SAR-X radar images (Scan SAR and Stripmap mode) were collected and analysed, from January 2011 until May of 2014. From image segmentation and feature extraction, 38 oceanic eddies have been detected. Three different categories of oceanic spiral formations were determined, depending on their pixel and texture characteristics. The majority of detected eddies were sub-mesoscale eddies with low backscatter signature, related with algal blooms and biogenic material occurrence, combined with low wind and current velocities. Their diameter varied from 1 to 9 km and the formations were located near regions with irregular topography and semi-closed Gulfs. During intermediate western winds, sub-mesoscale eddies with higher backscatter signatures were detected, with diameter variation from 3,5 km to 6,5 km. These formations were related with surface circulation and located near regions where surface currents circulation altered. On the Northern part of the basin, during winter season, sub-mesoscale eddies due to ice interaction were detected close to density and temperature front regions. These formations presented high backscatter coefficient values and smoother texture than the other sub-mesoscale eddies categories. Their diameter varied from 2 to 7 km. Most of the detected sub-mesoscale eddies were smaller or equal to baroclinic Rossby radius of deformation, which was varying from 1.5 to 7.2 km annually. The detected oceanic spirals were both cyclonically and anti-cyclonically rotated at the same abundance. In conjunction with acquisition date of the SAR images, sea surface temperature (SST) and chlorophyll (chl-a) concentration images from MODIS were collected for each date of detected oceanic eddies. In addition, wind speed data and current model data for surface circulation with sufficient spatial resolution were analysed in order to detect changes and correlations in the regions of the spiral formation detection. This approach was quite challenging due to different spatial resolutions of the datasets. From each dataset, plots and maps were generated, showing the overall conditions in the basin, as well as in the region were eddies detected. The majority of the sub-mesoscale eddies were located in regions of sharp shear changes or surface temperature fronts. From the combined information layers, strong correlation was concluded for eddies presenting low backscatter signatures with high temperatures and chlorophyll concentration. In contrast, the other two categories of eddies were generated in regions with low temperature and strong wind and current velocities, formed away from the coastline. As overall, the number of detected eddies was significantly lower than in studies focused on previews years. The detected categories of sub-mesoscale eddies were related to separable physical conditions and the presents results could help in their identification on SAR images.
CRIS-Team Scopus Importer:2024-03-18